MAJOR ENGINEERING DEPARTMENT IN CONDITIONS OF HIGHER EDUCATION REFORMING - Igor N. Kim (Moscow Polytechnic University, 2016)
Engineering education now faces the problems closely connected with the necessity to find new forms of education process organization. In these conditions the issue of teaching personnel retraining should be mentioned in the first place. The paper focuses on a role of a department responsible for core curricular programs development and discusses the status of a department chair and the principles of teaching staff formation. The chair must be a reputable scholar who holds a crucial leadership position. The chair is responsible for curriculum, planning, budget matters, personnel management, and for the department development. Besides, the chair must be a good practitioner in industrial work in order to establish external relations with enterprises and coordinate students' professional formation. One of the most effective and useful instruments to raise the quality of department activities is rating assessment of faculty in the main areas for definite periods. The author dwells on the problem of "feminization" of faculty members in engineering universities, women's predominance even in exceptionally "male" specialties.